INCLUSION CONTROL MODEL IN THE LADLE METALLURGY FURNACE - Pérez, Jorgelina (My University, 2012)
The inclusions are harmful to the steel cleanliness; process parameters such as stirring and steel and slag oxidation must be controlled to obtain a final number of inclusions in the steel whose size is smaller than the critical size for each steel product.
A simple mathematical model was developed to analyze the impact of bubbling, slag and initial oxidation level on inclusion distribution control (quantity and size of them) during the process in a Ladle Metallurgy Furnace (LMF).
The initial inclusion size distribution is calculated and adjusted with the samples analyzed by SEM-EDAX, this initial distribution decreases by removal mechanisms such as bubbling and slag and they can increases by reoxidation.
The model allows predicting the inclusion removal by bubbling mechanism as a function of gas flow rate and inclusion size and it proves which a softer stirring is better for removal inclusion than stronger one. An interesting point analyzed is the effect of stirring level on small and large inclusions.
According to the inclusion number removal by slag, it is possible to appreciate like larger inclusions are removed easier than smaller ones. This mechanism is the most important to remove inclusions calculated by this model.
Keywords: model; inclusion; ladle metallurgy furnace; bubbling; slag; steel; Metallurgy; Metallurgy